2006
DOI: 10.1186/1471-2296-7-8
|View full text |Cite
|
Sign up to set email alerts
|

Setting directions for capacity building in primary health care: a survey of a research network

Abstract: BackgroundThe South Australian Research Network 'SARNet' aims to build research capacity in primary health care, as part of a national government-funded strategy to integrate research into clinical practice. Internationally, research networks have been a fundamental part of research culture change, and a variety of network models exist. The 'SARNet' model uses a whole system, multidisciplinary approach to capacity building and supports individuals and groups. We undertook a descriptive baseline survey in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
87
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(91 citation statements)
references
References 5 publications
4
87
0
Order By: Relevance
“…Therefore, engaging clinical SLPs as part of the research workforce is not a matter of merely stimulating interest levels, but also needing to address perceived organisational challenges and skill development. As Reid et al (2006) concluded after finding a similar pattern in primary healthcare workers, a global approach is required to build research capacity in the healthcare setting.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, engaging clinical SLPs as part of the research workforce is not a matter of merely stimulating interest levels, but also needing to address perceived organisational challenges and skill development. As Reid et al (2006) concluded after finding a similar pattern in primary healthcare workers, a global approach is required to build research capacity in the healthcare setting.…”
Section: Discussionmentioning
confidence: 99%
“…Other strategies that have been suggested to increase research capacity include encouraging SLPs to undertake research higher degrees (Finch et al, 2013;Iles & Davidson, 2006;MacEwan Dysart & Tomlin, 2002), establishing links with universities (Reid et al, 2006), creating allied health dedicated research positions in healthcare settings, and mentoring with more experienced colleagues (Queensland Government, 2013: Reid et al, 2006. Additional support could be achieved by establishing a local or national research special interest group for SLPs engaged in research activities to share their experiences with likeminded colleagues (Reid et al, 2006). Interestingly, many participants in the present study, both engaged and not engaged in research, were interested in participating in a research special interest group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations